IJCM_81A: A Qualitative Study to Analyze the Awareness and Attitude of Type 2 Diabetes Mellitus Patients and Other Potential End-users on mHealth Applications for Disease Management. - Skaria Geena Mary; Sabu K M; Reshmi Bhageerathy; Shetty Sahana (Wolters Kluwer Medknow Publications, 2024)
Background: Diabetes requires intense multidisciplinary management techniques based on which the disease management strategies are adjusted to control the blood glucose values. There are numerous digital diabetic management applications available online, but Indian subscribers to such applications are minimal when compared with the diabetes population in India. The COVID-19 pandemic has seen a tremendous increase in the use of glucometers and other digital applications, which is a promising factor in propagating the idea of effective usage of mHealth applications. Objective: To analyze awareness and attitudes among the major digital health application stakeholders toward using mHealth applications in managing Type 2 Diabetes Mellitus (T2DM). Methodology: An in-depth interview (IDI) was conducted among T2DM patients, their caregivers, Doctors, and Diabetes counselors (that includes, nursing counselors, and diet counselors) in the endocrinology department of a tertiary care hospital in South India. Result: The findings revealed that the T2DM patients, despite knowing mHealth applications for T2DM management, are not very fond of using any of them for various reasons such as language and technology barriers, complexity of handling the application, and following application instructions. Conclusion: It was evident that there is a growing need to create awareness about the advantages of using digital applications for disease management and develop user-oriented, user-friendly applications for better acceptance of digital devices.